Nutrient retention by the littoral vegetation of a large lake: Can Lake Ohrid cope with current and future loading?. (26th May 2020) - Vermaat, Jan E.; Matzinger, Andreas; Trajanovska, Sonja; Talevska, Marina; Schneider, Susanne C.
Abstract: Nitrogen and phosphorus budgets were compiled for the littoral (29 km 2 ) and pelagic (329 km 2 ) of ancient, deep, clear, and hard water Lake Ohrid (Albania and North Macedonia), to assess the importance of the littoral in nutrient retention. P originates mainly from domestic point sources (73%), for N this is karst seepage (50%). Total littoral loads are estimated at 1700 kg P and 23, 200 kg N km −2 (area of littoral) yr −1 ; net littoral retention is 31% ± 13% for P and 40% ± 16% for N, largely in the dense charophyte belt. P retention is mainly due to detritus burial, but also due to coprecipitation; N retention is due to both detritus burial and denitrification. A Monte‐Carlo plausibility analysis balanced the budget by increasing nonconnected domestic household inputs (from 20% to 27% of external load), and decreasing pelagic sediment P burial by 27% and littoral denitrification by 25%. Scenario projections for 2100 corresponding to SRES A2 and B1 were linked to an AQUASIM lake ecosystem model. Under B1, the changes were small compared to the present. A2, however, led to a major reduction in precipitation, an increase in evapotranspiration, a reduction in river outflow (to ∼ 20%), a doubling in P‐loading, a drop in lake level of ∼ 1.5 m, and a decline in the extent of the charophyte belt. Areal loading of the littoral would increase accordingly, but water transparency would not decline much. Also, the littoral vegetation will witness a shift in species composition, and an increase in filamentous Cladophora cover.